Closed-orbit dependence on the field direction in the anisotropic diamagnetic Kepler problem - Bruno-Alfonso, A. [UNESP]; Bleasdale, C.; De Souza, G. V.B. [UNESP]; Lewis, R. A. [UNESP] (American Physical Society (APS), 2014)
The classical orbits of an electron with anisotropic mass interacting with a Coulomb center in the presence of a magnetic field are investigated. It is shown that the shape and duration of the closed orbits depend on the magnetic-field direction. Reasonable agreement with available experimental results for donor-doped silicon samples in a magnetic field is found, when the energy value of the conduction electron is appropriately chosen. © 2014 American Physical Society.